Optimizing Regulations in the Code of Ethics for Students: A Case Study of a SMKN in Palangkaraya City - Sarah Priskila Eksely; Yuli Handriani; Sharmila; Veny Marselina; Tania (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to optimize the regulations in the code of ethics carried out by students at one of the SMKNs in Palangka Raya City. In addition, the research aims to determine the level of discipline and efforts to improve student discipline in obeying school rules at SMK. Then, giving sanctions to students who commit violations is a motivating factor for students to always instill discipline. This study used a qualitative approach in collecting data using observation, interviews and documentaries. The results of the study show that student discipline is good enough, but efforts still need to be made to improve it because various violations of student discipline still exist even though they are only minor violations.